Battling Instability? The Recurring Logic of French Military Interventions in Africa. Issue 1 (2nd January 2017) - Powell, Nathaniel K.
ABSTRACT: This article examines continuities in the logic of postcolonial French military activism in Africa. It examines the long history of major French interventions on the continent, pointing to historically recurring views of threats, decision-making processes, and impact on the ground. Using this historical perspective, it evaluates the strategy and prospects of current French efforts in the Sahel. This article argues that French policy has largely failed in its stabilization goals. Principally, this is because it has strengthened the very factors at the source of the instability that France has aimed to contain.